Formulary for laboratory animals - Hawk, Terrance (Iowa State University Press/ Ames, 1999)
The electronic version of the print reference book. Includes hypertext-linked table of contents and index and a fully functional search engine for quick searches of the entire reference. Index and Contents entries are linked to the text for quick access